정치 유튜브 개인 방송에서 ‘정파성’은 어떻게 발현되는가? : 청년 정치 유튜버의 심층 인터뷰를 중심으로 - 정금희(Kum Hee Jung) (언론정보연구, 2021)
본 연구는 뉴스가 엔터테인먼트 서비스가 되는 중심에 들끓고 있는 ‘유튜브 저널리즘 현상’에 주목하고, 그 현상에서 새로운 뉴스 공급원으로 부상한 정치 유튜브 개인 방송을 연구주제로 삼았다. 1인 미디어로 정치 채널을 운영하는 청년 유튜버 6인을 심층 인터뷰하여, 언론 비전문가이지만 어떻게 정치 시사 관련 동영상을 제작하며 정치 채널을 운영하는지 그 과정을 면밀히 살펴보았다. 인터뷰가 진행됨에 따라 기존 언론과 정치 유튜브의 가장 도드라진 차이점으로 ‘공표된 정파성’을 꼽을 수 있다고 판단하여, ‘정치 유튜브 개인방송에서 정파성은 어떻게 발현되는가’를 최종 연구 문제로 심화하였다. 연구 결과, 정치 유튜브 정파성의 발현은 정치 채널 운영 흐름에 따라 4가지 차원으로 제시되었다. 첫째 ‘동기’ 단계는 정파성을 표명하고 채널을 시작하는 과정, 둘째 ‘규범’ 단계는 나름의 정파적 성향에 따라 새로운 규범을 만들고 축적해나가는 성장 과정, 셋째 ‘압박’ 단계는 이용자 및 유튜브 환경에서 요구된 정파적 압력에 갈등하고 ‘적정선’을 찾아가는 위기의 국면이다. 마지막으로 ‘집단 정파성’은 동일한 정치색을 띤 정파적 시청 공동체를 결성하고, 동기, 규범, 압박 등 모든 과정에서 영향을 미치는 요인으로 작동한다. 본 연구는 아직 개념화가 완성되지 않는 유튜브 저널리즘 현상에 대한 학술적 논의를 더욱 현실감 있는 높이와 거리에서 조명했다는데 의의를 찾는다. This study pays attention to the “Youtube journalism phenomenon,” where news are served as a entertainment and focuses on the political YouTube personal broadcastings, which has emerged as the most characteristic of that phenomenon. In-depth interviews were conducted with six young YouTubers who are operating their own political channels alone, in order to see how they perform the process of producing political content even though they are not professionals in journalism. As the interview progressed, it could be found out that the most prominent difference between the existing media and political YouTube was ‘manifested partisanship’, and the final research question was decided ‘how the Partisanship is being revealing in the political YouTube personal broadcastings.’ As a result of the study, YouTube political Partisanship could be understood in four dimensions according to the progress of political channel developing and maintaining. The first is a ‘motivation’ stage in a level of starting a channel, the second is a ‘norms’ stage as a growth process that creates and accumulates new norms according to its own political convictions, and the third is a ‘pressure’ stage demanded by users and YouTube environments. It is a phase of crisis in which they might have some conflict with a lot of kinds of environmental demands, so they have to search for the ‘appropriate choice’ for their political convictions as well as for their benefit from supporting. Finally, the last dimension is a ‘collectivity’ stage formed by users community with the same political partisanship and affect all processes, including ‘motivation, norms, and pressure’. This study is meaningful in that it could shed light on the political YouTube personal broadcasting as a discussion of Youtube journalism, which has yet to be conceptualized, at a more realistic and close height of view. KCI Citation Count: 0